Mental Fatigue and Spatial References Impair Soccer Players' Physical and Tactical Performances - Coutinho, Diogo; Gonçalves, Bruno; Travassos, Bruno; Wong, Del P.; Coutts, Aaron J.; Sampaio, Jaime E (Frontiers in Psychology, 2017)
This study examined the effects of mental fatigue and additional corridor and pitch sector lines on players’ physical and tactical performances during soccer small-sided games. Twelve youth players performed four Gk+6vs6+Gk small-sided games. Prior to the game, one team performed a motor coordination task to induce mental fatigue, while the other one performed a control task. A repeated measures design allowed to compare players’ performances across four conditions: (a) with mental fatigue against opponents without mental fatigue in a normal pitch (MEN), (b) with mental fatigue on a pitch with additional reference lines (#MEN); (c) without mental fatigue against mentally fatigued opponents on a normal pitch (CTR); and (d) without mental fatigue on a pitch with reference lines (#CTR). Player’s physical performance was assessed by the distance covered per minute and the number of accelerations and decelerations (0.5-3.0 m/s2; > -3.0 m/s2). Positional data was used to determine individual (spatial exploration index, time synchronized in longitudinal and lateral directions) and team-related variables (length, width, speed of dispersion and contraction). Unclear effects were found for the physical activity measures in most of the conditions. There was a small decrease in time spent laterally synchronized and a moderate decrease in the contraction speed when MEN compared to the CTR. Also, there was a small decrease in the time spent longitudinally synchronized during the #MEN condition compared to MEN. The results showed that mental fatigue affects the ability to use environmental information and players’ positioning, while the additional reference lines may have enhanced the use of less relevant information to guide their actions during the #MEN condition. Overall, coaches could manipulate the mental fatigue and reference lines to induce variability and adaptation in young soccer players’ behavior.